Comparison Between Sleeve Gastrectomy and Exenatide on Type 2 Diabetic Patients - ELBASAN, ONUR (MARY ANN LIEBERT, INC, 2020)
Background: Diabetes and obesity are major causes of mortality and morbidity that are increasing all over the world. As obesity is a major risk factor for type 2 diabetic patients, weight loss is important in the treatment of type 2 diabetic patients. In our study, our aim was to evaluate the effects of exenatide and laparoscopic sleeve gastrectomy (LSG) in obese type 2 diabetic patients on the clinical and laboratory parameters. Methods: Twenty-five LSG and 25 exenatide patients followed up in our outpatient clinic were involved in the study. Results: At the end of the 6-month follow-up, weight loss was similar to 35.4 kg in the surgery group and 11.5 kg in the exenatide group. Although postprandial glucose and hemoglobin A1c were significantly decreased in both groups, the decrease was significantly higher in LSG group compared to the exenatide group. Although there was no significant change in fasting blood glucose (FBG) in the exenatide group, there was a significant decrease in FBG in LSG group. Conclusion: LSG is a method that should be performed up on indication and much more radical compared to exenatide administration, but appears to be a more efficient application that corrects diabetes- and obesity-related metabolic parameters compared to exenatide therapy in type 2 diabetic obese patients.
Keywords: bariatric surgery; exenatide; obesity; T2DM; CARDIOVASCULAR RISK-FACTORS; BARIATRIC SURGERY; OBESE-PATIENTS; HEPATIC BIOMARKERS; RECEPTOR AGONISTS; INTERIM ANALYSIS; MEDICAL THERAPY; EFFICACY; MANAGEMENT; WEIGHT